Digital education strategies around the world: practices and policies. Issue 1 (2nd January 2022) - Gabriel, Florence; Marrone, Rebecca; Van Sebille, Ysabella; Kovanovic, Vitomir; de Laat, Maarten
ABSTRACT: Technology is omnipresent in our rapidly changing digital world. Capitalising on these technologies is paramount for education systems to support a modern workforce. This study presents a review of 10 countries, highlighting how different public education systems have integrated digital technologies for teaching and learning. These education systems were selected based on their high performance and continuous improvement in international assessments. Four main themes emerged as key areas of focus from our analysis: improved and enhanced teaching and learning; digital maturation, including tackling the first and second digital divide; data-driven decision making and evidence-based education; and AI in education. Our findings will help benchmark current approaches and uses of digital teaching and learning, including perceived challenges and opportunities that can be used to inform the development and implementation of digital education policies.